Pelatihan Guru Biologi dan Siswa SD-SMA/SMK di Pontianak untuk Meningkatkan Pengalaman Belajar di Bidang Bioteknologi - Mursyanti, Exsyupransia; Stefani Santi Widhiastuti; Dewi Retnaningati (Jurnal Atma Inovasia, 2022)
Abstract — Pontianak is the center of education in the province of West Kalimantan. In the implementation of education and learning, the interaction between competent teachers and active students can improve the quality of education. Therefore, a service activity was made that aims to ensure quality educational services in accordance with the times. This service activity is entitled Training and Assistance for Biology Teachers and Elementary-SMA/SMK Students at Karya Yosep Elementary School, St. Peter's Middle/High School, St. Mary's Vocational School with the theme Biotechnology and its Applications for the Welfare of Human Life. The method used is contextual learning which is packaged with a webinar model which includes 2 sessions, namely the delivery of material and discussion sessions. This activity is divided into 3 stages, namely the preparation, implementation, and evaluation stages. Overall, the activity went smoothly. This activity can increase the knowledge of Biology teachers and students in partner schools about the field of biotechnology, and participants can practice and apply the material received in everyday life. More than 85% of the participants from the group of teachers, elementary-junior high school students, and high school/vocational school students thought that the material provided was in accordance with the needs.Keywords — training, teachers, students, biotechnology.